Screening The Effectiveness of Menirans Leaf Extract (Phyllanthus niruri L.), Pepaya (Carica papaya L.), and Kunyit (Curcuma longa L.) as Antidengue In Vitro - Hutami Sri Ummiyati; Ratih Puspita Febrinasari; Leli Saptawati (Nexus Biomedika, 2016)
Introduction: Dengue Haemorrhagic Fever (DHF) is an infectious disease that is caused by dengue virus. There were 71.668 DHF cases with 641 mortalities in Indonesia which was recorded from early January to mid-December 2014. Recently, DHF doesnt have a specific therapy. The aim of this study was screening about natural extracts in Indonesia as antidengue. Methods: This study was a laboratory experimental research with dengue virus serotype 2 strain New guinea C (DENV2 NGC) as a subject. This virus was infected into Huh-7 cell line. The study was conducted in 2 parts. First, dengue virus solution was mixed with natural extract and then this solution was infected to Huh-7 cell monolayer to obtain percent infectivity by FFU assay. Second,the natural extract was exposed to Huh-7 cell monolayer to obtain percent viability by MTT assay. The effective extract was selected if the extract had average percent infectivity 20% and average percent viability > 50%. Results: The percentage of viability of menirans leaf extract (Phyllanthus niruri L.), papaya (Carica papaya L.), and turmeric (Curcuma longa L.) were 96.2%, 97.5%, and 88.7% respectively. While their average percentage of infectivity were 63.9%, 10.5%, and 53.6%. Conclusion: The papayas leaf extract (Carica papaya L.) was effective as antidengue in vitro. Keywords: DENV2 NGC,dengue, meniran, papayas leaf, turmeric